Competing invaders: Performance of two Anguillicola species in Lake Bracciano. Issue 1 (April 2015) - Dangel, K.C.; Keppel, M.; Le, T.T.Y.; Grabner, D.; Sures, B.
Highlights Two Anguillicola spp. occurring as nonindigenous species are compared in the review. Both species differ in their life cycles. Anguillicola crassus replaced Anguillicola novaezelandiae in Lake Bracciano. Possible reasons for the disappearance of A. novaezelandiae are discussed.